Physical and dispersive optical characteristics of ZrON/Si thin-film system - Wong, Y.H. (Springer Verlag (Germany), 2014)
To date, the complex evaluation of physical and dispersive optical characteristics of the ZrON/Si film system has yet been reported. Hence, ZrON thin films have been formed on Si(100) substrates through oxidation/nitridation of sputtered metallic Zr in N2O environment at 500, 700, and 900 ∘C. Physical properties of the deposited films have been characterized by X-ray diffractometry (XRD), Fourier transform infrared (FTIR) spectroscopy, reflection high-energy electron diffraction (RHEED), and spectroscopic ellipsometry (SE). It has been shown that ZrON/Si thin films without optical absorption can be prepared by oxidation/nitridation reaction in N2O environment at 700–900 ∘C.